Long-term training effects on masticatory muscles - Hellmann, Daniel; Giannakopoulos, Nikolaos Nikitas; Blaser, Ralf; Eberhard, Lydia; Rues, Stefan; Schindler, Hans J. (Journal of oral rehabilitation, 2011)
Neuromuscular adaptations during skill acquisition have been extensively investigated for skeletal muscles. Motor rehabilitation is the main target for application of motor training. Such measures are also relevant for the musculature of the jaw, but few data are available for motor adaptation of the masticatory system. The objective of this study was to evaluate and compare long-term training effects of different motor tasks on masseter and temporal muscles. In 20 healthy subjects, the electromyographic response to unilateral and bilateral maximum voluntary tooth clenching, balancing the mandible on a hydrostatic system under force-feedback-controlled conditions, and unilateral chewing was investigated in an initial session and then in two follow-up sessions separated by 2 and 10 weeks from baseline. Motor tasks were repeated three times for chewing, nine times for maximum biting (MB) and 24 times for the coordination tasks (CT). The sequences of the various motor tasks were applied once in the first session and twice in the second and third sessions. No effects of training were observed for MB tasks except for MB in intercuspation, for which significant yet transient avoidance behaviour occurred in the second session. No significant effects were found for chewing tests. For the CT, however, a robust significant long-term training effect was detected which reduced the electric muscle activity in session 2 by approximately 20% and in session 3 by approximately 40% compared with the initial measurements. The study showed that the masticatory muscles are remarkably prone to motor adaptation if demanding CT must be accomplished.
First published: 13 May 2011
Gesehen am 04.10.2022